Production, optimization, and physicochemical characterization of biodiesel from seed oil of indigenously grown Jatropha curcas - Haq, Abdul; Laiq Ur Rehman, Mian; Rana, Qurrat ul Ain; Khan, Alam; Sajjad, Wasim; Khan, Haji; Khan, Samiullah; Shah, Aamer Ali; Hasan, Fariha; Ahmed, Safia; Islam, Arshad; Badshah, Malik; et al. (Frontiers in Energy Research, 2023)
With the growing demand for vegetable oils, alternative non-edible feedstocks like Jatropha curcas seed oil have gained interest for biodiesel production. The study aimed to comprehensively evaluate the physicochemical properties and biodiesel production potential of locally produced J. curcas seeds in Pakistan. Two different approaches were applied: a chemical synthesis approach involving acidic pretreatment and alkaline transesterification, and a biosynthetic approach using a lipase-producing strain of the Bacillus subtilis Q5 strain. The microbial biosynthesized biodiesel was further optimized using the Plackett–Burman design. The physicochemical properties of the J. curcas methyl esters were analyzed to assess their suitability as biodiesel fuel. Initially, the raw oil had a high free fatty acid content of 13.11%, which was significantly reduced to 1.2% using sulfuric acid pretreatment, keeping the oil to methanol molar ratio to be 1:12. Afterward, alkaline transesterification of purified acid-pretreated seed oil resulted in 96% biodiesel yield at an oil to methanol molar ratio of 1:6, agitation of 600 revolutions per minute (RPM), temperature 60°C, and time 2 h. Moreover, alkaline transesterification yielded ∼98% biodiesel at the following optimized conditions: oil to methanol molar ratio 1:6, KOH 1%, time 90 min, and temperature 60°C. Similarly, the Bacillus subtilis Q5 strain yielded ∼98% biodiesel at the following optimized conditions: oil: methanol ratio of 1:9, agitation 150 RPM, inoculum size 10%, temperature 37°C, and n-hexane 10%. The fuel properties of J. curcas seed biodiesel are closely related to standard values specified by the American Society for Testing and Materials (ASTM D6751–20a), indicating its potential as a viable biodiesel fuel source.